Small vs. Young Firms across the World : Contribution to Employment, Job Creation, and Growth - Ayyagari, Meghana; Demirguc-Kunt, Asli; Maksimovic, Vojislav (2012)
This paper describes a unique cross-country database that presents consistent and comparable information on the contribution of the small and medium enterprises sector to total employment, job creation, and growth in 99 countries. The authors compare and contrast the importance of small and medium enterprises to that of young firms across different economies. They find that small firms (in particular, firms with less than 100 employees) and mature firms (in particular, firms older than 10 years) have the largest shares of total employment and job creation. Small firms and young firms have higher job creation rates than large and mature firms. However, large firms and young firms have higher productivity growth. This suggests that while small firms employ a large share of workers and create most jobs in developing economies their contribution to productivity growth is not as high as that of large firms.